Peer to Peer Video on Demand Architecture using V-Chaining - K, Hareesh; D. H, Manjaiah (INTERNATIONAL JOURNAL OF COMPUTERS & TECHNOLOGY, 2012)
In the Internet, video streaming requires greater amount of network bandwidth and other resources as the number of user requests increases. In case of traditional centralized directory server approach all the users requests are directly handled by the centralized server and each user request will send dedicated stream by the server, which requires higher end server, server cost will become more and greater amount of network bandwidth utilized by this server. To solve these problems peer to peer technology as emerged for the distribution of video streams to the larger requests over the network. In P2P VoD architecture adopted both the peer to peer and proxy based architectural design of a VOD system for larger community of users over the network. Hence our proposed Peer to Peer Video on Demand Architecture using V-Chaining improves the overall performance of the system by efficient utilization of uplink bandwidth and smaller amount of buffer space among the peers. In this paper we have introduce architecture for handle the large number of user requests over the communication network and ease of implementation.